BUDAYA RELIGIUS DALAM MENINGKATKAN PROFESIONALISME DOSEN PENDIDIKAN AGAMA ISLAM FITK UIN MALIKI MALANG - Munir, Misbah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
The institution is now faced with the challenges of globalization and the increased flow of technology very quickly. This phenomenon became the motivation for educational institutions to continue to learn and improve to work more professional in his field. The institution also responds to the presence of the desire of the community to the services of quality education, to be realized it can be done through a process of planned, terpola, and tersistematisasi through an educational process that leads to the realm of cognitive, affective, psychomotor. In addition, it can also be done through establishing a conducive campus culture through the creation of religious culture on campus, through activities such as the obligatory prayers in congregation activities, recite the Koran, do prayers together, the process of teaching started by reading al-fatiha and continued with reading Koran together, after it finishes with reading hamdalah together and use a neat muslim muslimah clothing at work.